Creating The List of Proposed Records to Be Destroyed In Records Retention Activities at Perum Bulog - Adriansyah, Muhammad Farhan; Grataridarga, Niko; Safitri, Dyah (International Journal of Cultural and Social Science, 2024)
BULOG Public Company (Perum BULOG) is a State-Owned Enterprise which operates in the food logistics sector and is responsible for the supply and distribution of basic commodities in Indonesia. In carrying out its activities, Perum BULOG produces various important documents and records such as agreements, accommodation, insurance, moving costs and logistics orders. Therefore, efficient records management is a must. One of the key elements in records management is retentention and disposition by destroying records that are no longer needed for efficient records storage. Before carrying out destruction, the organization must create a list of records proposed for destruction so that the recordss to be destroyed can have news metadata recorded and become a reference for vital recordss for the destruction event. This article discusses the process of creating a list of records proposed for destruction which is carried out at Perum Bulog with the aim of ensuring that records are stored properly according to their retention period, as well as maintaining the quality of records management so that they can support the organization's tasks more effectively.